2022
DOI: 10.1111/gcb.16370
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil greenhouse gas emissions to land use conversion and reversion—A global meta‐analysis

Abstract: Exploring the responses of greenhouse gas (GHG) emissions to land use conversion or reversion is significant for taking effective land use measures to alleviate global warming. A global meta-analysis was conducted to analyze the responses of carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O) emissions to land use conversion or reversion, and determine their temporal evolution, driving factors, and poten-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 84 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…From each raster gradient, ~52.94% of the mean vegetation NPP growth proportion increased in four provinces of Southwest China from 2000 to 2020 (Appendix S1: Table S2). For example, we found that NPP increased obviously in the range 800–1500 g C m −2 year −1 , which should be related to the impact of the GGP in China (Bryan et al, 2018; Feng et al, 2022). Previous studies also indicated that NPP increased along with the increase in conversion forest and grassland areas after the GGP (Chen, Wang, et al, 2018; Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…From each raster gradient, ~52.94% of the mean vegetation NPP growth proportion increased in four provinces of Southwest China from 2000 to 2020 (Appendix S1: Table S2). For example, we found that NPP increased obviously in the range 800–1500 g C m −2 year −1 , which should be related to the impact of the GGP in China (Bryan et al, 2018; Feng et al, 2022). Previous studies also indicated that NPP increased along with the increase in conversion forest and grassland areas after the GGP (Chen, Wang, et al, 2018; Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…6c ), and the RRd of CH 4 emissions showed a negative relationship with the RRd of soil bulk density (Fig. 7a ), implying that the lower soil bulk density in the restored grasslands increased CH 4 diffusion from atmosphere into soils and thus increased CH 4 uptake 44 . Grassland restoration by reducing grazing intensity or grazing exclusion increased belowground biomass (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…6a ). The higher SOC concentrations in the restored wetlands could provide more substrates for methanogen growth than in the paired control ecosystems 44 , 56 . Thus, elevating the water table level and increasing the substrate supply for methanogen is likely to result in higher CH 4 fluxes in the restored wetlands (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations